Epigenetic regulation of CXCR4 signaling in cancer pathogenesis and progression - Reem Khaled M.E. Alsayed (17563251) (2022)
Signaling involving chemokine receptor CXCR4 and its ligand SDF-1/CXL12 has been investigated for many years for its possible role in cancer progression and pathogenesis. Evidence emerging from clinical studies in recent years has further established diagnostic as well as prognostic importance of CXCR4 signaling. CXCR4 and SDF-1 are routinely reported to be elevated in tumors, distant metastases, which correlates with poor survival of patients. These findings have kindled interest in the mechanisms that regulate CXCR4/SDF-1 expression. Of note, there is a particular interest in the epigenetic regulation of CXCR4 signaling that may be responsible for upregulated CXCR4 in primary as well as metastatic cancers. This review first lists the clinical evidence supporting CXCR4 signaling as putative cancer diagnostic and/or prognostic biomarker, followed by a discussion on reported epigenetic mechanisms that affect CXCR4 expression. These mechanisms include regulation by non-coding RNAs, such as, microRNAs, long non-coding RNAs and circular RNAs. Additionally, we also discuss the regulation of CXCR4 expression through methylation and acetylation. Better understanding and appreciation of epigenetic regulation of CXCR4 signaling can invariably lead to identification of novel therapeutic targets as well as therapies to regulate this oncogenic signaling. Other Information Published in: Seminars in Cancer Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.semcancer.2022.03.019